(untitled) (Global Journal of Human-Social Science, 2021)
Ensuring human rights especially humane treatment of women is one of the most pressing issues in the modern world A historical fact idea or scientific conclusion that serves the interests of all mankind is of particular importance Today a certain part of the world s population is made up of Muslims It is no secret that Islamic culture and scientific heritage have a special place in human history But unfortunately there are many conflicting views on the understanding and interpretation of Islamic teachings and procedures and most importantly on their implementation As a result misconceptions are emerging in the Muslim community itself as well as in the minds of people of other faiths In this case one of the best solutions is to first learn and know how it was and in what order it was used This paper analyzes the situation of the first prophetic mission in the Meccan period on the basis of the verses of the Qur an revealed at that time There are also verses on proposing solutions to economic problems Most importantly this article provides objective insights into the attitude towards women their participation in social events and the portrayal of women in the Qur an in the prophetic mission of Meccan period